THE ROLE OF EMPLOYMENT ENGAGEMENT AND ORGANIZATIONAL TRUST ON EMPLOYEE PERFORMANCE: MEDIATION OF JOB SATISFACTION IN PANDEMIC CONDITION FOR PUBLIC SERVICES EMPLOYEES - Linda Bangkit Sugesti (Journal of Management and Islamic Finance, 2021)
The purpose of this study is to determine the influence of work engagement and organizational trust by mediating job satisfaction on employee performance during the pandemic for employees in the public service sector. The type of research was quantitative. This study used primary data with a sample in this study of 103 respondents taken from employees of the public service sector. The sampling technique used purposive sampling. Data collection method was by distributing questionnaires. Analysis technique of PLS (Partial Least Square) was through SEM-PLS software with Smart PLS 3.0. The results indicate that job satisfaction and work engagement have a significant positive effect on employee performance in public service employees. Job engagement has a significant positive effect on job satisfaction. Organizational trust has no significant effect on job satisfaction and also on employee performance. Job satisfaction is not able to mediate the effect of organizational trust on employee performance. Meanwhile, work engagement has a significant effect on employee performance by mediating job satisfaction of employees in the field of public services. The results of this study reinforce the importance of the role of employee engagement in increasing job satisfaction which in turn will lead to increased employee performance.